PENGARUH KEPATUHAN SYARIAH, DEWAN PENGAWAS SYARIAH, DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN: (Studi Empiris pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode 2017 – 2020 ) - Resmawati, Sonah; Kristanto, Eri; Sutarti, Sutarti (JURNAL EKONOMI, 2022)
This study aims to determine the effect of sharia compliance as proxied by profit sharing ratio, islamic income ratio, and zakat performance ratio, sharia supervisory board, and audit commitee on financial performance (Empirical Study on Islamic Commercial Banks Registered with the Financial Authority (OJK) for the 2017 – 2020 period). The sampling technique used is purposive sampling. The type of data used is secondary data and the total sample used in this study is 8 Islamic Commercial Banksare used as samples. Statistical analysis in this study used multipled linier regression. The result of this study indicate that, Sharia Compliance as a proxied by Profit Sharing Ratio has no effect on Financial Performance, Islamic Income Ratio has no effect on Financial Performance, Zakat Performance Ratio has negative effect on Financial Performance. Sharia Supervisory Board has no effect on Financial Performance. Audit Commitee has no effect on Financial Performance. Sharia Compliance, Sharia Supervisory Board, and Audit Commiteeno effect the Financial Performance.